2004
DOI: 10.1086/425737
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Neutron Star Spin Frequency in EXO 0748-676

Abstract: We report the results of a search for burst oscillations during thermonuclear X-ray bursts from the low mass X-ray binary (LMXB) EXO 0748-676. With the proportional counter array (PCA) onboard the Rossi X-ray Timing Explorer (RXTE) we detected a 45 Hz oscillation in the average power spectrum of 38 thermonuclear X-ray bursts from this source. We computed power spectra with 1 Hz frequency resolution for both the rising and decaying portions of 38 X-ray bursts from the public RXTE archive. We averaged the 1 Hz p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 20 publications
10
95
1
Order By: Relevance
“…Larger spin rates, assuming a NS radius of around 10 km, would wash out such a line unless the surface emission is confined to a narrow region around the spin axis ( Bhattacharyya et al 2004). A slow rotation rate for EXO 0748À676 is consistent with the recently measured 44.7 Hz burst oscillation ( Villarreal & Strohmayer 2004). With these line profiles in hand, and assuming that the burst oscillation of 44.7 Hz is the rotation rate of the NS, detailed fits to the data raise the exciting prospect of fitting for the NS radius (Chang et al 2005).…”
Section: Discussionsupporting
confidence: 78%
“…Larger spin rates, assuming a NS radius of around 10 km, would wash out such a line unless the surface emission is confined to a narrow region around the spin axis ( Bhattacharyya et al 2004). A slow rotation rate for EXO 0748À676 is consistent with the recently measured 44.7 Hz burst oscillation ( Villarreal & Strohmayer 2004). With these line profiles in hand, and assuming that the burst oscillation of 44.7 Hz is the rotation rate of the NS, detailed fits to the data raise the exciting prospect of fitting for the NS radius (Chang et al 2005).…”
Section: Discussionsupporting
confidence: 78%
“…We confirm the finding of Villarreal & Strohmayer (2004), that the widths of these features are consistent with formation at the surface of a star with a spin rate of 45 Hz. We have also shown that stars with spin rates up to $600 Hz can produce lines this narrow if emission from close to the rotational axis dominates.…”
Section: Discussionsupporting
confidence: 90%
“…First, it is detected in the brightest burst with significance at the 99.96% confidence level, not in a whole set of six bursts (Kaaret et al 2007). Second, from a statistical point of view, the frequency of 1122 Hz is too far outside the range of the previously known spin frequencies of LMXBs, from the minimum value of 45 Hz (Villarreal & Strohmayer 2004) to the maximum of 619 Hz (Hartman et al 2003), centered at ∼400 Hz , and it is much higher than the fastest spin frequency of radio pulsars, 716 Hz (Hessels et al 2006). Therefore, we take this spin frequency of 1122 Hz as a tentative detection, or the possibility might be considered that the signal of 1122 Hz is merely a candidate burst oscillation (e.g., Galloway 2007 By means of this assumed highest spin frequency, we can constrain the NS mass and radius, which indicates the frequency of 1122 Hz to be close to the centrifugal breakup limit for some equations of state of nuclear matter (e.g., Burgio et al 2003).…”
Section: Consequences and Discussionmentioning
confidence: 85%